Vault dehiscence two years after total abdominal hysterectomy: A case report - Jessica Benton; Honor Mijatovic; Belinda Lowe (Case Reports in Women's Health)
Vault dehiscence is a rare but significant complication of hysterectomy that can result in bowel evisceration through the vagina. This condition occurs when there is separation of the surgically created vaginal cuff, which can lead to serious morbidity, including bowel evisceration, ischaemia, and peritonitis. Vault dehiscence usually occurs in the months following a hysterectomy, but there have been a few case reports of late vaginal vault dehiscence. This report explores the case of a 48-year-old multiparous menopausal woman who presented to the emergency department with unprovoked vaginal cuff dehiscence, on a background of open hysterectomy two years prior. The patient had undergone a laparoscopic hiatal hernia repair two weeks prior to her presentation at the emergency department with dehiscence, raising the question of whether that laparoscopic procedure was related to the presentation with vault dehiscence because it had resulted in weakness of the vaginal vault. She underwent emergency laparoscopic surgery to examine the eviscerated bowel and repair the vault defect. This case report outlines the risk factors for vault dehiscence and factors which may be associated with late and unusual presentations of vault dehiscence after hysterectomy.